ANALISIS DAMPAK PERPANJANGAN MASA JABATAN KEPALA DESA TERHADAP PENGELOLAAN SUMBER DAYA DAN KINERJA PERANGKAT DI DESA GANDON KECAMATAN KALORAN KABUPATEN TEMANGGUNG - Abdurrahman, Danna Muhamad Bagas; Muhtada, Dani (JOURNAL EQUITABLE, 2025)
This study aims to analyze the effect of the extension of the term of office of the village head on resource management and the performance of village officials in Gandon Village, Kaloran Subdistrict, Temanggung Regency. The formulation of the problem raised includes the effect of the extension of the term of office on the management of village resources and the performance of village officials. The method used in this research is empirical juridical research with a statutory approach and interviews as data collection techniques. The results showed that the extension of the term of office of the village head can provide stability in leadership, which supports more effective planning and implementation of development programs. However, there are challenges in the form of potential delays in elite circulation and gaps in technological understanding among village officials. Community involvement in the decision-making process and transparency in village financial management are important factors to maintain public accountability and participation. This study recommends the need for training for village officials and increased community participation to achieve better development outcomes in the village.